2013
DOI: 10.1074/jbc.m113.501817
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Substrate Diversity and Preference of Small Heat Shock Protein IbpB as Revealed by Using a Genetically Incorporated Photo-cross-linker

Abstract: Background:The identity of natural substrate proteins of small heat shock proteins is poorly understood. Results: A total of 95 and 54 natural substrate proteins were identified for IbpB in living cells at 50 and 30°C, respectively. Conclusion: IbpB preferentially protects translation-related proteins and metabolic enzymes. Significance: This study offers mechanistic insights into the chaperone functions of small heat shock proteins for cells against stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 65 publications
0
57
0
1
Order By: Relevance
“…Uniquely, the sHSPs of both prokaryotic and eukaryotic sources have also been found to be associated with cell membranes (34)(35)(36)(37)(38). Over the years, we have tried to delineate the function and mechanism of sHSPs, from largely bacterial sources, via both in vitro and in vivo studies (39)(40)(41)(42)(43)(44)(45). To study the function and mechanism of sHSPs in C. elegans, we first focused on CeHSP17, which remains the least characterized such proteins in terms of function and properties among the small heat shock proteins of C. elegans (46) and is predicted by our bioinformatics analysis to be putatively localized in mitochondria (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Uniquely, the sHSPs of both prokaryotic and eukaryotic sources have also been found to be associated with cell membranes (34)(35)(36)(37)(38). Over the years, we have tried to delineate the function and mechanism of sHSPs, from largely bacterial sources, via both in vitro and in vivo studies (39)(40)(41)(42)(43)(44)(45). To study the function and mechanism of sHSPs in C. elegans, we first focused on CeHSP17, which remains the least characterized such proteins in terms of function and properties among the small heat shock proteins of C. elegans (46) and is predicted by our bioinformatics analysis to be putatively localized in mitochondria (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a total of 94 proteins in the cell extract of bacterium Deinococcus radiodurans were found to co-aggregate with Hsp20.2 during thermal treatment [56]. Importantly, we have recently identified a total of 113 cellular proteins interacting with IbpB in living E. coli cells by using in vivo photo-crosslinking [54]. Retrospectively, these natural substrate proteins of specific sHSPs appear to have a variety of cellular functions, such as metabolism (e.g.…”
Section: Functional Diversity Of the Substrate Proteins Of Shspsmentioning
confidence: 99%
“…To clarify this, database searching was performed for three representative human sHSPs regarding their interacting partners. The results presented in Table 1 indicated that aB-crystallin binds a number of cellular proteins, including Hsp16.6-bound proteins after heat shock were co-purified, with 13 being identified [81]; IbpA-bound proteins were co-purified, with 42 being identified [82]; IbpB-bound proteins were covalently photo-crosslinked with IbpB in living cells and then co-purified, with 113 being identified [54]; Hsp20.2-bound proteins were co-purified from the thermally treated mixture of Hsp20.2 and cell extract, with 94 being identified [56]. The information for mammalian sHSPs-bound proteins was extracted from the protein-protein interaction databases (a uniform entry is provided at http:// www.ebi.ac.uk/Tools/webservices/psicquic/view/main.xhtml).…”
Section: Functional Diversity Of the Substrate Proteins Of Shspsmentioning
confidence: 99%
See 2 more Smart Citations